The COVID-19 as mediation to the survival of the collective: The demerit of necessity and individual freedom through the perspective of work geography - Carvalho , Raymond Socrates de Castro; Carvalho , Glaucely Ramos Figueiredo (Seven Editora, 2023)
This article deals with the importance of the role of work as a founding condition of the social being and its repercussions in the actions that determine the conditions of collective needs that metabolize the man-environment relationship. The reality that the transformations imposed by the Covid-19 pandemic made emerge in the scope of space and global territorial perspective, the feelings of tenacity that individuals have come to external, as behavior in the social environment, abdicating the freedoms and individual needs, imposed by the market, through the neoliberal logic and reproduction of capital. DOI:https://doi.org/10.56238/emerrelcovid19-072